Synthesis and characterization of a novel paramegnetic polyaniline composite with uniformly distributed metallic nanoparticles sandwiched between polymer matrices - Khanam, Z.; Sa'don, N.A.; Adam, F. (Elsevier, 2014)
Polyaniline (PANI) is among one of the most extensively studied electroconductive polymers. The present study involves synthesis of novel sandwiched PANI composite, where cobalt complexes were embedded in between PANI layers. Uniform dispersion of complex on polyaniline matrix was carried out in acetonitrile at room temperature via magnetic agitation of polyemeraldine base and Co-complex solution mixtures. Spectroscopic studies (FT-IR, FT-Raman, UV–vis and 15N MAS NMR) have evidenced the interaction of Co-complex with the N-backbone of polymeric chain. The lamellar structure of composite as well as existence of metal containing spherical nanoparticles of Co[SalophH2]2+ ions between them were detected in TEM micrographs with average diameter of 4.78 nm. The thermogravimetric analysis of the prepared nanocomposite displayed four stages of degradation between 29.4 and 897.2 °C with considerable thermal stability. Moreover, determination of magnetic properties of all the prepared materials showed that PANI-Co[SalophH2]-PANI composite has paramagnetic behavior, while PANI and its emaraldine base were diamagnetic in nature at room temperature. Thus, the present study holds promise for thermal purposes and magnetic applications of cobalt containing polyaniline composites.